Inkonsistensi Struktur dan Makna Backronim pada Tagline Universitas Al Azhar Indonesia - Hadiansyah, Dhuha; Bawarti, Era; Sabbah, Sherien; Herwandar, ria (Universitas Al Azhar Indonesia, 2025)
Backronyms play an important role in branding by creating taglines that strengthen brand identity and build emotional connections, supporting effective marketing strategies. For universities as socialpreneurship or edupreneurship entities, the use of backronyms can enhance visibility and attract prospective students, helping to achieve long-term goals. This study analyzes the backronyms